2017
DOI: 10.1053/j.gastro.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Esophageal Mucosal Afferent Nerves May Contribute to Reflux Hypersensitivity in Nonerosive Reflux Disease

Abstract: Proximal and distal esophageal mucosa of patients with NERD have more superficial afferent nerves compared with controls or patients with ERD or BE. Acid hypersensitivity in patients with NERD might be partially explained by the increased proximity of their afferent nerves to the esophageal lumen, and therefore greater exposure to noxious substances in refluxate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 39 publications
1
71
1
Order By: Relevance
“…The historical cohorts were used for comparison . HV comprised 10 patients with a mean age of 24 years (range: 21‐42 years), NERD (normal endoscopic appearances and increased esophageal acid exposure, ie, “true” NERD): 13 patients, seven male, with a mean age of 50 years (range: 28‐75 years).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The historical cohorts were used for comparison . HV comprised 10 patients with a mean age of 24 years (range: 21‐42 years), NERD (normal endoscopic appearances and increased esophageal acid exposure, ie, “true” NERD): 13 patients, seven male, with a mean age of 50 years (range: 28‐75 years).…”
Section: Resultsmentioning
confidence: 99%
“…Biopsies were analyzed alongside other samples from patients with gastro‐esophageal reflux disease (GERD) by a research team member who was blinded as to which were from FH patients. Biopsy processing was exactly as previously described . After orientation, biopsies were fixed in 4% paraformaldehyde for 3 hours, followed by cryoprotection in 30% sucrose in phosphate‐buffered saline (PBS) for 24 hours at 0.4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although dysphagia may be associated with neurologic impairment and anatomic diseases that can affect these swallowing stages, the symptom may also result from esophageal hypersensitivity and/or hypervigilance, without any alteration in the oral, pharyngeal or esophageal transit (9,26) . In patients with non-erosive GERD, proximal and distal esophageal mucosa have more superficial afferent nerves compared with no reflux disease or patients with erosive disease and patients with Barrett esophagus (27) . Patients with extra esophageal manifestations of gastroesophageal reflux frequently have non-erosive disease in esophagus (15) , with the possibility to have more superficial afferent nerves and hypersensitivity in proximal esophageal body, explaining the possibility of dysphagia in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that TRPV1 receptors are expressed in afferent neuronal fibers, as observed in biopsies of patients with NERD, and in non‐neuronal cells, such as esophageal epithelial cells . A recent study demonstrated CGRP‐positive nerves close to the esophageal lumen in patients with NERD, which colocalized with TRPV1‐immunoreactive nerve fibers in mouse esophagus . Thus, further investigations are necessary.…”
Section: Discussionmentioning
confidence: 99%